Amplified Drought Alters Leaf Litter Metabolome, Slows Down Litter Decomposition, and Modifies Home Field (Dis)Advantage in Three Mediterranean Forests - Quer, Elodie; Pereira, Susana; Michel, Thomas; Santonja, Mathieu; Gauquelin, Thierry; Simioni, Guillaume; Ourcival, Jean-Marc; Joffre, Richard; Limousin, Jean-Marc; Aupic-Samain, Adriane; Lecareux, Caroline; Dupouyet, Sylvie; et al. (Plants (Basel, Switzerland), 2022)
In Mediterranean ecosystems, the projected rainfall reduction of up to 30% may alter plant-soil interactions, particularly litter decomposition and Home Field Advantage (HFA). We set up a litter transplant experiment in the three main forests encountered in the northern part of the Medi-terranean Basin (dominated by either Quercus ilex, Quercus pubescens, or Pinus halepensis) equipped with a rain exclusion device, allowing an increase in drought either throughout the year or concentrated in spring and summer. Senescent leaves and needles were collected under two precipitation treatments (natural and amplified drought plots) at their "home" forest and were left to decompose in the forest of origin and in other forests under both drought conditions. MS-based metabolomic analysis of litter extracts combined with multivariate data analysis enabled us to detect modifications in the composition of litter specialized metabolites, following amplified drought treatment. Amplified drought altered litter quality and metabolomes, directly slowed down litter decomposition, and induced a loss of home field (dis)advantage. No indirect effect mediated by a change in litter quality on decomposition was observed. These results may suggest major alterations of plant-soil interactions in Mediterranean forests under amplified drought conditions.
Keywords: litter quality; metabolomics; experimental drought; Home Field Advantage (HFA); Mediterranean forest